Adjustment of College Students in Relation to Their Well Being (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2012)
Education in changing scenario meets the requirements for development of a country. Education is the best media for all round development of human personality. Education is the process to train the students for adjustment in the life situations. Main concern of teachers is to develop the capacity among the students for adjusting in home, school, college and in the society. The adjustment is a life long process and continuous till the end of life. Vonhaller (1975) defined adjustment as a psychological survival. Rizvi (2011) stated that an adjusted person enjoy in creating something new and useful for others.